Development of a Physical Education Learning Model for Badminton Using the Sport Education Model Approach to Improve Learning Outcomes of Junior High School Students - rahman, arif rahman; pamot rahardjo, hermawan; Aji_putra, Ranu Baskora (Journal of Physical Education and Sports, 2025)
This research is based on the problem, including the low learning outcomes of badminton material. This research aims to: (1) analyze the development of physical education learning of badminton material using the sport education model approach for junior high school students. (2) Analyze the feasibility of physical education learning of badminton material using the sport education model approach for junior high school students. (3) Analyze the effectiveness of physical education learning of badminton material using the sport education model approach for junior high school students. This research method uses R&D Brog and Gall. Small-scale trials were implemented on 30 students and large-scale trials on 60 grade IX students. Data analysis includes feasibility tests, student response tests, effectiveness tests, and paired tests. The study results are as follows: (1) expert validation one feasibility percentage 88%, expert validation two feasibility percentage 98%, and expert validation three feasibility percentage 81%. (2) small-scale results of paired tests, sig 0.00 <0.05 (significant), effect size 0.8 (large). (3) large-scale paired sig test 0.00<0.05 (significant) and effect size 1.4 (extensive) Based on the results of data analysis, the physical education learning product of badminton material with a sports education model approach for junior high school students is declared feasible. This learning product can help teachers in the teaching and learning process of junior high school physical education. Based on the results of data analysis, the physical education learning product of badminton material with a sport education model approach for junior high school students is declared feasible. It can support teachers in the teaching and learning process of PJOK junior high school.